Rozwiąż równanie: [latex] frac{x}{ sqrt{3} } = 2sqrt{3} -x[/latex]

Rozwiąż równanie: [latex] frac{x}{ sqrt{3} } = 2sqrt{3} -x[/latex]
Odpowiedź

[latex] frac{x}{ sqrt{3}}=2 sqrt{3}-x/* sqrt{3}\ x=6- sqrt{3}x\ x+ sqrt{3}x=6\ x(1+ sqrt{3})=6\ x= frac{6}{1+ sqrt{3}} \ x= frac{6}{1+ sqrt{3}}* frac{1- sqrt{3}}{1-sqrt{3}} = frac{6-6 sqrt{3}}{-2}=-3+3 sqrt{3} [/latex]

Dodaj swoją odpowiedź
Matematyka

Rozwiąż równanie: [latex] frac{2 - sqrt{2} }{3 sqrt{3} - x} + 2sqrt{2} =4[/latex]

Rozwiąż równanie: [latex] frac{2 - sqrt{2} }{3 sqrt{3} - x} + 2sqrt{2} =4[/latex]...

Matematyka

Proszę o zrowiązanie tych zadań: 1. Rozwiąż równainie [latex]frac{(x - sqrt{5})(1 + 2sqrt{5})}{2}- xsqrt{5}=0[/latex]   2. Rozwiąż równanie [latex](2x - 1)^{2} - (2x +1)^{2} = x^{2}[/latex]

Proszę o zrowiązanie tych zadań: 1. Rozwiąż równainie [latex]frac{(x - sqrt{5})(1 + 2sqrt{5})}{2}- xsqrt{5}=0[/latex]   2. Rozwiąż równanie [latex](2x - 1)^{2} - (2x +1)^{2} = x^{2}[/latex]...

Matematyka

Rozwiąż równanie:   [latex]frac{2-sqrt{2}}{3sqrt{3}-x}+2sqrt{2}=4[/latex]     Z góry dziękuje ;)

Rozwiąż równanie:   [latex]frac{2-sqrt{2}}{3sqrt{3}-x}+2sqrt{2}=4[/latex]     Z góry dziękuje ;)...